1988
DOI: 10.1185/03007998809114237
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trial of intra-articular injection of sodium hyaluronate in patients with osteoarthritis of the knee

Abstract: A multi-centre randomized, double-blind, parallel-group clinical trial was carried out in 63 patients with osteoarthritis of the knee to compare the efficacy and tolerability of a course of intra-articular injections of 20 mg sodium hyaluronate with a similar course of injections of placebo. Treatment consisted of up to 11 injections over a 23-week period. Evaluation was by means of subjective symptom and activity assessments, serially during the course of treatment and also 25 weeks thereafter. Ten patients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(49 citation statements)
references
References 17 publications
1
48
0
Order By: Relevance
“…Sodium hyaluronate has been widely used for patients with various joint disorders. 24,25 However, injection of sodium hyaluronate into the TMJ cavity as well as drug administration and physiotherapy after pumping manipulation treatment may have biased the study results.…”
Section: Discussionmentioning
confidence: 99%
“…Sodium hyaluronate has been widely used for patients with various joint disorders. 24,25 However, injection of sodium hyaluronate into the TMJ cavity as well as drug administration and physiotherapy after pumping manipulation treatment may have biased the study results.…”
Section: Discussionmentioning
confidence: 99%
“…12,16,28,30,31,37 Sixteen trials reported that the outcome observer was blinded to the intervention. 12,16,18,20,22,23,[26][27][28][29][30][31][32][33]35,37 Two trials did not present any usable quantitative information. 30,35 Therefore, only 22 trials were included in the analysis of at least 1 of the predefined efficacy end points (Fig.…”
Section: Trial Qualitymentioning
confidence: 99%
“…Many randomized controlled studies have demonstrated a longer-term effect in pain control with HA injections compared with corticosteroids [31] and placebo [32,33]. Hyaluronic acid has approximately a 1% incidence of side effects per injection.…”
Section: Discussionmentioning
confidence: 99%